2011
DOI: 10.1111/j.1445-2197.2011.05753.x
|View full text |Cite
|
Sign up to set email alerts
|

Public perception of the field of plastic surgery

Abstract: The general public's understanding of plastic surgery is poor. This may be linked to the misunderstanding of specialist titles and lack of education regarding this field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 7 publications
3
43
0
Order By: Relevance
“…In addition, "no plastic surgeon" was significantly more recognized as an expert in different general/reconstructive-related scenarios. These findings demonstrated that the broad scope of plastic surgery practice is poorly recognized and widespread among the Brazilian public, similar to previously described trends in surveys [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] of medical students, medical residents, nurses, and primary care physicians, among others.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…In addition, "no plastic surgeon" was significantly more recognized as an expert in different general/reconstructive-related scenarios. These findings demonstrated that the broad scope of plastic surgery practice is poorly recognized and widespread among the Brazilian public, similar to previously described trends in surveys [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] of medical students, medical residents, nurses, and primary care physicians, among others.…”
Section: Discussionsupporting
confidence: 64%
“…However, analyses performed on each scenario showed that plastic surgeon was primarily recognized as an expert in aesthetic-related scenarios and less identified in fundamental interventions for plastic surgery as a broad-based medical specialty, mirroring previous data [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. In addition, "no plastic surgeon" was significantly more recognized as an expert in different general/reconstructive-related scenarios.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations